Puberty and breeding performance of beef heifers developed at different rates of gain - J. Ernest Minton; Robert T. Brandt Jr.; C.M. Coughlin; R.C. Cochran (Kansas Agricultural Experiment Station Research Reports, 1994)
Crossbred heifers (546 lb initial body weight) were developed in drylot and limit-fed a corn, corn silage diet to gain .5 (n = 14), 1.0 (n = 15), 1.5 (n = 14), or 2.0 lb/d (n = 15) from Dec. 7, 1992 until the onset of the breeding season, May 3, 1993. Actual daily gains averaged 1.0, 1.4, 1.8, and 2.1 lb/d, respectively. Age at puberty was not affected by feeding treatment. At the onset of the breeding season, nutritional treatment had a linear effect on body condition score, ribeye fat thickness (both P<.01), and reproductive tract score (P<.05), all increasing with increasing rate of gain. Nutritional treatment had a quadratic effect on pelvic area (P<.05), which averaged 190.6, 201.6, 206.5, and 205.3 cm2 for heifers fed to gain .5, 1.0, 1.5, and 2.0 lb/d, respectively. At the conclusion of the development period, estrus was synchronized, and heifers were inseminated artificially at estrus for 45 days and, if open, mated naturally for another 17 d. Overall pregnancy rates were similar among heifers fed to gain .5, 1.0, and 1.5 lb/d (92.9, 93.3, and 92.9%, respectively), and all tended to be greater (P<.09) than the rate for heifers fed to gain 2.0 lb/d (66.7%). In summary, NRC recommendations underestimated gain of limit-fed heifers at lower predicted rates of gain. Thus, even though heifers fed to gain only .5 lb/d had lower body condition scores and reproductive tract scores at the onset of the breeding season, their actual body weight gains (1.0 lb/d) were sufficient for normal onset of puberty and subsequent conception. In addition, heifers fed to achieve relatively high rates of gain (2.0 lb/d) during development may have had impaired fertility.
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Beef heifers; Puberty; Heifer development